Exploring Teachers’ Meta-Discourse in Mother Tongue within English Medium Instruction (EMI) Content Classrooms in Sri Lanka - Leelachandra, D. (University of Jaffna, 2025)
This study investigates the role of teachers’ meta-discourse in their mother tongue within English Medium Instruction (EMI) content classrooms, focusing on Higher National Diploma (HND) programmes at a higher education institute in Sri Lanka. The primary aim is to identify and analyse the functions fulfilled by mother tongue meta-discourse during classroom interactions. Adopting a qualitative research design, data were collected through audio recordings of naturally occurring teacher talk across multiple sessions in Accountancy, Management, and Information Technology classrooms. These were transcribed and analysed manually, with attention to recurring instances of mother tongue use functioning as meta-discourse. Supplementary data from classroom observations and semi-structured interviews with lecturers were triangulated to validate the findings and provide contextual depth. The data analysis followed a thematic approach, drawing on discourse analytic techniques to identify the patterns and pragmatic functions of such language use. Findings reveal that teachers’ use of mother tongue meta-discourse serves several pedagogical functions, including organising classroom discourse, clarifying complex concepts, managing classroom routines, scaffolding learner understanding, and encouraging student participation. A key finding in the study is how the use of mother tongue meta-discourse in EMI contexts is not merely compensatory but strategic, contributing to meaning-making, relational dynamics, and cognitive access. The study also finds that such practices are largely intuitive rather than systematically planned, highlighting a gap in pedagogical awareness. These insights emphasise the educational value of teacher code alternation in EMI settings and suggest the need for reflective teacher training that recognises and refines these instinctive practices. The study offers implications for both EMI policy and pedagogical development, particularly in multilingual higher education contexts.
Keywords: Teacher meta-discourse; EMI content classrooms; Mother tongue in classrooms